Exploring the Levels of eLearning Interactivity: A Review of Research Literature - Ismail, Alajab Mohammed Alajab (Journal of Ecohumanism, 2024)
eLearning has become a widespread and integral part of modern education and training. A key aspect of effective eLearning is interactivity, which can enhance engagement, learning, and knowledge retention. This paper provides a comprehensive review of the research literature on the levels of interactivity in eLearning environments. The review examines different taxonomies and frameworks proposed to categorize and assess the various levels of interactivity, from low-level interactions such as clicking and scrolling, to more advanced interactive features like simulations, virtual reality, and collaborative learning tools. The paper also discusses the pedagogical benefits of increasing interactivity, as well as the design and implementation considerations for achieving optimal levels of interactivity in eLearning. Finally, the review identifies gaps in the current research and suggests future directions for studying the impact of interactivity on eLearning outcomes.